(untitled) (Research, Society and Development, 2024)
This article presents a technical analysis of the inefficiency of the microdrainage system in São Luís Street, located in the center of the city of Açailândia, state of Maranhão. The research aims to identify and understand the main problems related to microdrainage in this specific area, bounded by Rio Grande do Norte and Bonaire Streets. Using data collection methods such as field observations, deficiencies in the drainage system were identified, resulting in flooding and inconvenience to the local population. The main causes of inefficiency include the inadequate sizing of drainage structures, lack of proper maintenance, and the accumulation of trash on public roads. Based on the results obtained, corrective measures are proposed to mitigate the problems identified, such as redesigning the drainage system, implementing regular maintenance practices, and making the population aware of the importance of preserving the microdrainage system. It is believed that the implementation of these measures will contribute to improve drainage conditions and reduce the negative impacts caused by inefficient microdrainage on São Luís Street and the surrounding areas.